- Evaluating the financial performance of listed insurance companies in the Saudi stock market - An Empirical Study - Al Saadi, Faisal Fahad Mohammed (Journal of Economic, Administrative and Legal Sciences, 2018)
The current study aimed to examine the effect of internal factors (financial planning, internal monitoring, managerial competency) and external factors (legal environment, economic environment, competitive environment) on the financial performance of insurance companies depending on the return on assets and return on equity. A descriptive methodology was applied on the research. The community consisted of (31) insurance company listed in Saudi stock market. Hence, questionnaires were distributed and targeted three managers from each company, the retrieved questionnaires were (78) to be analyzed using Statistical Package for the Social Sciences program (SPSS). The results indicated that there was no statistical differences regarding internal factors (financial planning, internal monitoring, managerial competency) and it effect on the financial performance of insurance companies depending on the return on assets and return on equity, moreover, there was no statistical differences regarding external factors (legal environment, economic environment, competitive environment) and it effect on the financial performance of insurance companies depending on the return on assets and return on equity. The study recommended that future studies should focus on other financial measurements to assess the financial performance of insurance companies like profit margin, debt percentage, liquidity percentage.